DEVELOPMENT OF ANDROID-BASES DIGITAL HANDOUT LEARNING MEDIA ON THE NEWS MATERIAL OF THE PROCLAMATION OF INDEPENDENCE IN PALEMBANG CLASS XI AT SMA NEGERI 12 PALEMBANG: Pengembangan Media Pembelajaran Handout Digital Berbasis Android Pada Materi Berita Proklamasi Kemerdekaan di Palembang kelas XI di SMA Negeri 12 Palembang - Dayanara Bening; Muhamad Reza Pahlevi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aimed to develop and evaluate an Android-based digital handout learning media focused on the Proclamation of Independence news in Palembang for 11th-grade history students at SMA Negeri 12 Palembang. The research addressed the need for engaging and locally relevant history learning materials, considering that existing resources were limited and students showed insufficient understanding of local historical events. The study employed a Research and Development (R&D) approach guided by the ADDIE instructional design model, consisting of analysis, design, development, implementation, and evaluation phases. Data collection involved curriculum analysis, interviews, questionnaires, and expert validation. The media was tested through one-on-one, small group, and full-class field trials, using pretests and posttests to measure student learning outcomes. Results showed a significant increase in student learning outcomes, with the average score improving from 45.48 in the pretest to 97.09 in the posttest. The N-gain value of 0.94 indicated high effectiveness of the media. Expert validation confirmed the product’s validity in terms of content, media design, and language. Students responded positively to the media’s clarity, interactivity, and accessibility via smartphones. While the media proved effective and well-received, limitations include the study’s focus on a single school and challenges faced by students without smartphone access. Future research should consider broader samples and alternative access methods to ensure inclusivity and generalizability.